ARCADIA fully depleted CMOS MAPS development with LFoundry 110 nm CIS - Da Rocha Rolo, Manuel; Andreazza, Attilio; Ambrosi, Giovanni; Alfonsi, Fabrizio; Balbi, Gabriele; Dalla Betta, Gian-Franco; Croci, Tommaso; Caccia, Massimo; Chiappara, Davide; Corradino, Thomas; Durando, Stefano; Falchieri, Davide; et al. (Frontiers in Sensors, 2025)
Fully depleted CMOS sensors represent a significant step forward in radiation detection, combining the advantages of monolithic active pixel sensors with the enhanced signal collection efficiency of depleted bulk materials. The ARCADIA Collaboration established a technology platform for the development and production of deep sub-micron fully depleted CMOS monolithic sensors with excellent collection efficiency, advancing this semiconductor detector technology with IP cores, ASICs, and back-end dedicated acquisition systems. The sensor technology was demonstrated on system-ready full chip monolithic active pixel sensors with high rate capability and very low power for the detection of charged particles and photons. Innovative CMOS monolithic LGADs featuring a shallow gain layer and implementing a low-gain avalanche diode were developed for time-of-flight detectors, while other prototype ASICs have implemented multi-threshold photon-counting architectures for X-ray imaging. The implementation of fully depleted monolithic strip sensors with embedded electronics and low power density makes the proposed approach a good candidate for future detectors in space applications. The ARCADIA technology will find applications in medical instruments, nuclear imaging and dosimetry, frontier detectors for experimental high energy, and astroparticle physics. This review details the main development achievements by describing the technology demonstrators fabricated and tested and provides a detailed overview of the characteristics and architecture of the ARCADIA-MD3 full-chip monolithic active pixel sensor.